EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255974 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1052 ZenodoArchiveConcept: 13255973
Keywords: _r:AddedByMyEducationEvidence

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub)
PreviousDOI: 10.5281/zenodo.4476897 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4476897 10.5281/zenodo.4556940 2339240:GU8FEH69 2339240:W9GJBGT9 2405685:FEXJQ37Q 2405685:ZPTMAP5C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted